Lorimer, Jamie i Hodgetts, Timothy (2024). More-than-Human - Xavier Oliveras González (Documents d'Anàlisi Geogràfica)
Lorimer, Jamie i Hodgetts, Timothy (2024) More-than-Human Londres: Routledge, 262 p. ISBN 9781138058392